The effects of cutting parameters on machining performance of titanium alloy Ti-5553 - (:unkn) unknown (TAYLOR & FRANCIS LTD, 2019)
New-generation aerospace alloys gain more interest due to their advanced properties. Ti-5553 alloy can be categorised as new-generation aerospace alloys, but it is also difficult-to-machine material. For this reason, machining performance and the role of cutting parameters on machining of this particular alloy needs to be well investigated. This study aims to contribute to understand machining performance of Ti-5553 under various cutting parameters including cutting speed, feed rate and depth of cut. Machining performance tests were carried out without using any cooling and lubricant. Tool wear, cutting forces, chip breakability and surface quality were considered as measured machining performance criteria. This study reveals that the depth of cut and cutting speed have a profound effect on the machining performance of this material by substantially affecting tool wear and cutting temperature and thus all measured machining performance outputs.
Keywords: Titanium Ti-5553 alloy; tool wear; cutting force; surface roughness; CHIP FORMATION; TOOL-WEAR; MACHINABILITY; MQL; SPEED; DRY